Barriers and enablers to implementing tuberculosis control strategies in EU and European Economic Area countries: a systematic review. Issue 9 (September 2021) - Conroy, Olivia; Wurie, Fatima; Collin, Simon M; Edmunds, Matt; de Vries, Gerard; Lönnroth, Knut; Abubakar, Ibrahim; Anderson, Sarah R; Zenner, Dominik
Summary: Meeting the 2035 WHO targets of reducing tuberculosis incidence by 90% from 2015 levels requires the implementation of country-specific tuberculosis control strategies. This systematic review aims to identify factors that facilitate or impede the implementation of such strategies in EU and European Economic Area (EEA) settings. Focusing on providers of care, health system constraints, and social and political factors, this Review complements available evidence on the accessibility of tuberculosis services to recipients of care. Databases were searched for EU and EEA articles published between Jan 1, 1997, and Nov 6, 2020, that presented empirical data on tuberculosis policies, strategies, guidelines, or interventions. 2061 articles were screened and 65 were included. The most common barrier to tuberculosis control strategies described the divergence of health-care practices from guidelines, often related to inadequate knowledge or perceived usefulness of the guidelines by clinicians. The most commonly identified enabler to tuberculosis control strategies was the documented positive attitudes of health-care workers towards tuberculosis programmes. Divergence between clinical practice and guidelines was described in most EU and EEA settings, indicating the need for a focused review of guideline adherence. Strengths of this study involve its broad inclusion criteria and wide range of tuberculosis control strategies analysed.